2013
DOI: 10.4236/ojoph.2013.33019
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Trabeculectomy in Africa

Abstract: Purpose:To determine the outcome of trabeculectomy in African countries. Design: This is a review of literature for trabeculectomy conducted in Africa from 2000 to December 2012. Methods: We conducted an electronic search from the following databases: PubMed, Science Direct, Google, and Google scholar websites for the articles of original studies on trabeculectomy conducted in Africa. Results: A total of 109 articles, published from 2000 to December 2012 were retrieved. Only 12 articles met our inclusion crite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Soatiana et al [13], comparing outcomes of Trabeculectomies across Africa reviewed studies from 5 Sub Saharan countries. For these studies IOP control was successful with a range of 10-22mmHg (drop of 61.8-90%).…”
Section: Discussionmentioning
confidence: 99%
“…Soatiana et al [13], comparing outcomes of Trabeculectomies across Africa reviewed studies from 5 Sub Saharan countries. For these studies IOP control was successful with a range of 10-22mmHg (drop of 61.8-90%).…”
Section: Discussionmentioning
confidence: 99%
“…More so, the surgeon may have to add a suture if the bleb is filtering too much or use a laser to cut a suture if the bleb is filtering too slowly (Jones, Clarke, & Khaw, 2005;Razeghinejad, & Spaeth, 2011;Leung, & Tham, 2013). Unlike most eye laser treatments which guarantee very quick recovery, it can take several weeks for the eye to recover from a trabeculectomy surgery (Soatiana et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Some of these complications are reversible, such as cataracts, because cataract surgery can be performed at a later date. Findings from the meta-analysis done in Africa regarding the outcomes of trabeculectomy surgery revealed that the success rate varied from 61.8% to 90% (post-operative IOP was between 10-20 mmHg) and that trabeculectomy done with or without application of anti-metabolite like Mitomycin C (MMC) yield good outcome regarding IOP control (Soatiana et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Trabeculectomy with or without application of anti-metabolite appears to be a good way of lowering the IOP in Africa [8].…”
Section: Introductionmentioning
confidence: 99%